1999
DOI: 10.1136/bjo.83.11.1268
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil versus cyclosporin A in high risk keratoplasty patients: a prospectively randomised clinical trial

Abstract: Background/aims-The requirement for an eVective, minimally toxic immunosuppressive agent remains a major obstacle to performing high risk corneal transplantation. Although therapy with cyclosporin A (CSA) allows superior graft survival, its use is limited because of a wide range of side eVects. Mycophenolate mofetil (MMF) has been shown to be a safe and eVective immunosuppressive agent following renal transplantation. This prospective, randomised clinical trial was carried out to investigate the eYcacy and saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
11

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 4 publications
0
50
0
11
Order By: Relevance
“…Side effects such as nephrotoxicity, hepatotoxicity, hypertension, altered glucose metabolism, and gingival hyperplasia occur in up to 40 % of patients [8,9], but probably the most threatening complication is the increased incidence of malignancy (cancers, lymphomas) [10,11]. Reis et al [12] and Birnbaum et al [9] showed Clinical Trial Registration number if required Not required.…”
Section: Introductionmentioning
confidence: 99%
“…Side effects such as nephrotoxicity, hepatotoxicity, hypertension, altered glucose metabolism, and gingival hyperplasia occur in up to 40 % of patients [8,9], but probably the most threatening complication is the increased incidence of malignancy (cancers, lymphomas) [10,11]. Reis et al [12] and Birnbaum et al [9] showed Clinical Trial Registration number if required Not required.…”
Section: Introductionmentioning
confidence: 99%
“…Side effects might lead to premature withdrawal of the immunosuppressive drug with a resulting higher risk for rejection. 12,23,24 Therefore, it is desirable to have a broader armamentarium of immunosuppressive agents offering a more favourable side effect profile and comparable efficacy in preventing graft rejection following penetrating high-risk keratoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…A kilökődési reakciók csökkentését jelentette a lokális kortikoszteroid alkalmazása mellett bevezetett peroralis immunmoduláns gyógyszer, amely kezdetben a cyclosporin A (CsA), majd a mycophenolat mofetil (MMF) volt [3]. Egyes klinikai vizsgálatok pedig azt mutatták, hogy a peroralisan adott antiherpeticum és az MMF erő-síti egymás hatását, a transzplantátum hosszú ideig recidívamentes marad, és kilökődési reakció sem lép fel [4].…”
Section: Postoperative Therapy Of Penetrating Keratoplasty In Herpes unclassified
“…Reis és mtsai [4] egy rövid tanulmányban felhívták a fi gyelmet, hogy MMF és AC együttes adása nullára csökkentette a recidívát és a re jectiót 15 beteg esetében 9 hónap alatt. Ugyanez a munkacsoport korábban CsA-t alkalmazott [3], de megállapították, hogy az MMF jobb hatású [13], aminek az az oka, hogy a két gyógyszer között szinergista hatás áll fenn. A peroralis antivirális és immunszuppresszív kezelés hatásosságát mások is bizonyították [11].…”
Section: Megbeszélésunclassified